Análisis e interpretación de los estados financieros y su aporte en la toma de decisiones en empresas de transporte - Rueda Rodriguez, Jacqueline del Cisne (2015)
The degree work is executed to know the financial and economic situation of the transport company TAXICOM S.A, for which it relies on the analysis and interpretation of financial statements in the period 2013 – 2014, which identifies the operational reality and financial thereof also detect the strengths and weaknesses of to solve them. The main objective of this research work is to establish basic financial indicators to improve control of their financial operations and making relevant decisions of the company in question. Financial indicators are established as the most effective tool for financial analysis on companies because allows to evaluate the financial position, the development and results of business activity in the present, past and predict the future, through calculations of indicators to guide management towards an efficient and effective financial application. The methodology for the implementation of financial analysis proceeded to obtain information on the financial situation of the company, analyze the two main and important financial statements as in the Statement of Financial Position and Statement of Comprehensive Income, determining and applying the basic financial indicators to detect the financial capacity and interpret results obtained being useful to evidence the condition that the company is situated. We conclude that the analysis using financial indicators that show the level of liquidity, the degree of solvency, efficiency, borrowing capacity and the level of profitability, of the business. It is recommended that this analysis and interpretation of financial statements is profitable to control financial transactions and measure their effectiveness, in order to generate profits by controlling costs and expenses.